Subspecies of Symbolic Capital within Ordinary Management - Euflausino, Mariana Aparecida; Ichikawa, Elisa Yoshie (Organizações & Sociedade, 2022)
The objective of this paper is to propose the acknowledgement of subspecies of symbolic capital in the context of everyday work practices within the framework of Ordinary Management, a perspective which is relevant and scarcely discussed in Administration. It consists of a perspective which is distant from the mainstream of Administration and fosters observation as a way to comprehend other forms of management related to the everyday life of the ordinary man. As a result, we reflect upon the necessity of acknowledging resources and capitals which are particular to this manner of performing management, in which economic and cultural capitals are lacking, and capitals must be observed based on their symbolic effects. We base the discussion of this proposal on the theoretical-epistemic approaches of Michel de Certeau, about the art of creating everyday life, and of Pierre Bourdieu, about the perspectives of symbolic capital within the context of the theory of practices. We assume the plurality of the concept of capitals but, moreover, we try to bring the understanding of capital closer to the reality of an Ordinary Management. Therefore, we propose an inversion of the common perspectives on capital, related to “distinction” and “glamour” and fostered by the dominant mindset in Administration. We suggest acknowledging subspecies of symbolic capital which inhabit the popular, the “vulgar” and, consequently, not “distinctive”. This paper contributes to organizational studies by opening up space for the recognition of the resources which configure the practices of management of small subsistence entrepreneurship, which express the everyday reality of businesses in the context of emerging countries.